2022
DOI: 10.33069/cim.2022.0030
|View full text |Cite
|
Sign up to set email alerts
|

Application of Transcranial Direct Current Stimulation in Sleep Disturbances

Abstract: Sleep disturbances are common across all age groups, and they encompass a broad range of impairments of daytime functioning and comorbid various clinical conditions. However, current treatment methods for sleep disturbances have several limitations. As the ‘top-down’ pathway is known to play an important role in sleep-wake regulation, and as neuronal activity abnormalities have been reported as a potential pathological mechanism of sleep disturbances, the use of non-invasive brain stimulation—such as transcran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 98 publications
1
1
0
Order By: Relevance
“…This heterogeneity can be caused by differences in the location, frequency, motor threshold of TMS stimulation, and the total session duration of TMS between the two studies. Additionally, the data used in the meta-analysis were not raw data from these two studies [23]. Consistent with the meta-analysis conducted by Zheng et al [14], it was found that TMS is most effective when administered for an extended period of up to 4 weeks.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This heterogeneity can be caused by differences in the location, frequency, motor threshold of TMS stimulation, and the total session duration of TMS between the two studies. Additionally, the data used in the meta-analysis were not raw data from these two studies [23]. Consistent with the meta-analysis conducted by Zheng et al [14], it was found that TMS is most effective when administered for an extended period of up to 4 weeks.…”
Section: Discussionsupporting
confidence: 67%
“…The mechanism of action of tDCS on DLPFC region involves modulating cortical stimulation, affect the top-down pathway that targets the corticothalamic pathway in regulating sleep-wake cycles. This modulation helps reduce hyperarousal and hyperactivity in the DMN and SN regions, leading to a decrease in sleep onset latency (SOL) and an increase in total sleep time (TST) [18,23]. It also triggers sleep waves and sleep spindles, especially in N2, and reduces the likelihood of transitioning from N2 sleep to wakefulness while increasing the transition from N2 to N3 [24,25].…”
Section: Introductionmentioning
confidence: 99%